Wearable Safety Device for Protecting Women from Harassment in a Public Place - Khushi Satish Singh; Priya Ramkumar Singh (International Journal of Electro-Mechanics and Material Behaviour, 2024)
Women's safety is currently an important issue in India. The crime rate against women in this country is only increasing rapidly. Women have to think twice before leaving the house, especially at night. Nowadays, in the current context of globalization, women face many challenges along with safety issues. There are many apps and devices available to ensure women's safety through smartphones. Although smartphones have developed rapidly, it is not always possible to have a phone in hand to make calls or press buttons, so here we have introduced a new technique through hidden wearable device. This device will be hidden and not visible, so when any women is at risk of sexual assault or is vulnerable, she can directly press the help me or emergency button.
Keywords: Protection; Safety; device; smart device; women